Earl crush ebook A novel. - Vasti, Alexandra (Belvoir's Library, 2025)
"Bridgerton at its sexiest . . . Crush? Ha. I'm in love with the earl!" – Eloisa James, New York Times bestselling author USA Today bestselling author Alexandra Vasti returns with another hot, hilarious Regency romp about a reclusive earl and the wallflower-turned-radical-pamphleteer who turns his life upside down. For three years, wallflower heiress Lydia Hope-Wallace has anonymously penned seditious pamphlets—and for almost as long, she's corresponded with the reclusive Earl of Strathrannoch. When Arthur's latest letter reveals his dire financial straits, Lydia sets out for Scotland to offer him the only salvation she can think of: a marriage of convenience. To, um, herself. But the real earl has no idea who she is. When a bewitching stranger offers him her hand in marriage, Arthur Baird is stunned. And when he learns that his traitorous brother has been writing to her under Arthur's name, he's bloody furious. He's content to live alone in his moldering castle, and he has no desire for a radical wife. (Or at least, he shouldn't.) But Arthur is desperate to track down his brother, who's become dangerously entangled in British espionage, and he needs Lydia's help. What he doesn't need? The attraction that burns hotter each moment they spend together. As Lydia slips past his defenses and his brother's mysterious past becomes a very present threat, Arthur will have to risk everything to keep her safe—even his heart. "Wildly delightful! With Earl Crush , Alexandra Vasti has crafted a marvelously funny and sexy read featuring a brawny Scottish earl, zebras, and a feminist heroine ahead of her time. This belongs on every romance reader's keeper shelf!" – Joanna Shupe, USA Today bestselling author of The Duke Gets Even "Vasti follows Ne'er Duke Well with another fiery and delightful Regency . . .This is a winner." – Publisher's Weekly